Мiнiмальна висота бар’єра для симетричних та несиметричних систем ядер - Denisov, V. Yu.; Margitych, T. O. (Publishing house "Academperiodika", 2019)
The interaction potential in symmetric and asymmetric systems composed of two nuclei has been studied with regard for the quadrupole, octupole, and hexadecapole deformations of nuclei. The influence of dynamic multipole deformations of the nuclear surface on the barrier height and the interaction energy between two nuclei is considered. The deformation parameters corresponding to the minimum values of barrier height are evaluated.